A study of phase separation processes in presence of dislocations in binary systems subjected to irradiation - Kharchenko, D.O.; Schokotova, O.M.; Bashtova, A.I.; Lysenko, I.O. (Condensed Matter Physics, 2015)
Dislocation-assisted phase separation processes in binary systems subjected to irradiation effect are studied analytically and numerically. Irradiation is described by athermal atomic mixing in the form of ballistic flux with spatially correlated stochastic contribution. While studying the dynamics of domain size growth we have shown that the dislocation mechanism of phase decomposition delays the ordering processes. It is found that spatial correlations of the ballistic flux noise cause segregation of dislocation cores in the vicinity of interfaces effectively decreasing the interface width. A competition between regular and stochastic components of the ballistic flux is discussed.